A Rare Case of Complex Hernia Causing Urethral Obstruction - Agrawal, Vivek; Bagla, Chinmay (The Surgery Journal, 2021)
Abdominal wall hernias rarely cause obstruction of the urinary tract. We present the case of a patient undergoing regular smooth dilatations for urethral stricture since 8 years who developed right inguinoscrotal swelling and narrowing of urinary stream since 2 years of age. There was a growing difficulty in dilatation due to path distortion of urethra by the hernia. He had a history of open suprapubic cystostomy (SPC) 8 years ago. The patient refused surgery till he landed with an inability to pass dilators and difficulty in passing urine. He was taken up for right inguinal exploration with internal optic urethrotomy (IOU). Intraoperatively, he was found to have right inguinal hernia with incisional hernia at the site of SPC which was repaired and a cystoscopy revealed urethral deviation with anterior urethral stricture for which IOU was done. Postoperatively, the patient's urethral tract straightened and his urinary complaints resolved. A complex hernia can cause urethral deviation and obstruction due to pressure effects of its contents and should be repaired at an early stage.
Keywords: complex hernia; urethral obstruction; urethral deviation